Performance analysis in manufacturing industry using QUEST simulation software / Zuriadi Mohamed and Mohd Afzakhairy Ahmad Farouk - Mohamed, Zuriadi; Ahmad Farouk, Mohd Afzakhairy (2004)
In the millennium era, softwares have becoming an important tools in word processing, database, spreadsheet, designing, simulating and others. Software will simplify, facilitate and ease human being in the manual job. This thesis intends to introduce to new users or entrepreneur about new manufacturing software called QUEST simulation software. The software is use to model floor layout in 3D simulation of a company. Beside of that, it also capable in modeling Computer Aided Design (CAD) in a 3D space such as AutoCAD, Solid Edge, Catia and etc. This thesis will provide a guide to the users on constructing a floor layout. By using the software, a lot of advantages can be obtain such as reducing time on rearranging the factory layout, saving costs, increase profit, increase productivity, reduce idle time, reduce lead time, and etc. From this thesis, a comparison between actual factory layout and QUEST factory layout is made to prove that the results will similar (by using all the data that are taken from the factory and applying the original layout). There are some errors that have to be considered such as human errors, machine errors and etc, but the result will remain the same.